Child Intoxication in the State of Paraná-Brazil - Filus, Rafaela Carolina Nascimento; Piran, Camila Moraes Garollo; Shibukawa, Bianca Machado Cruz; Cargnin, Alana Vitória Escritori; Oliveira, Natan Nascimento de; Furtado, Marcela Demitto (O Mundo da Saúde, 2023)
Intoxications constitute a worldwide public health issue. In Brazil, it is estimated that 33% of drug intoxication cases belong to children under nine years of age. This study aimed to analyze compulsory notifications of intoxication in children aged zero to nine years in the State of Paraná between the years 2016 and 2020. Using an epidemiological, descriptive study with a quantitative approach, the cases of notification due to child intoxication in the State of Paraná were examined from 2016 to 2020. Descriptive analysis and spatial distribution of the data were performed. As the study involved secondary data, ethical approval was not required. A total of 8,595 cases of child intoxication were reported during the study period. The age group of 1 to 4 years predominated (73.5%), as well as male gender (54.9%) and white ethnicity (73.1%). The most frequent toxic agents were medications (45%) and household products (20.5%). Regarding the type of exposure, acute-repeated exposure (93.6%) was the most common, with an outcome of cure without sequelae (94.8%). Cases of intoxication are linked to children in the early stages of life, emphasizing that many accidents can be prevented through proper product storage practices.